A method for preparing lithium iron phosphate positive electrode material
The sintering conditions of lithium iron phosphate are regulated through the two-step sintering method, which solves the problem of poor conductivity, significantly improves the rate performance, and is suitable for high-power lithium-ion batteries.
Patent Information
- Application Number
- CN202211713042.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-12-29
AI Technical Summary
The lithium iron phosphate prepared in the prior art has poor conductivity, resulting in poor rate performance, limiting its application in high-power lithium-ion batteries.
The lithium iron phosphate positive electrode material is prepared by two-step sintering method. By regulating the first and second sintering temperatures and time, as well as the relationship between the two-step sintering temperatures and time, the particle size of lithium iron phosphate obtained by sintering is optimized and its conductivity is improved. and lithium ion diffusion coefficient.
While ensuring that the discharge capacity is not lost, the conductivity and rate performance of lithium iron phosphate are significantly improved, and are suitable for high-power lithium-ion batteries.
Smart Images

Figure BDA0004027173690000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material technology, and in particular to a method for preparing a lithium iron phosphate positive electrode material. Background Art
[0002] Lithium iron phosphate (LiFePO4) occupies an irreplaceable position in lithium-ion battery positive electrode materials due to its advantages such as good cycle performance, high theoretical specific capacity (~170mAh / g), excellent thermal stability and low cost.
[0003] However, lithium iron phosphate has poor conductivity, resulting in poor rate performance, which seriously restricts the application of lithium iron phosphate in high-power lithium-ion batteries. Summary of the invention
[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defect of poor conductivity of lithium iron phosphate prepared in the prior art, thereby providing a method for preparing lithium iron phosphate positive electrode material.
[0005] To this end, the present invention provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:
[0006] The lithium source, the iron source, the phosphorus source and the carbon source are mixed and dried to obtain a premixed material;
[0007] In a protective gas atmosphere, heating the premixed material to a first sintering temperature T1 at a first heating rate, and sintering at the first sintering temperature T1 for a first time t1 to obtain a pre-sintered product;
[0008] Heating the pre-sintered product to a second sintering temperature T2 at a second heating rate, and sintering at the second sintering temperature T2 for a second time t2;
[0009] Among them, 400℃≤T1≤500℃, 2h≤t1≤6h, 660℃≤T2≤800℃, 6h≤t2≤10h, and 0.2≤(T2 / T1-1.3)×t2 / t1≤3.5.
[0010] Optionally, 400℃≤T1≤450℃, 4h≤t1≤6h, 660℃≤T2≤750℃, 6h≤t2≤8h.
[0011] Optionally, the first heating rate is 1 to 3°C / min;
[0012] Optionally, the second heating rate is 2-4°C / min.
[0013] Optionally, the particle size D50 of the premixed material is 4 μm to 8 μm.
[0014] Optionally, the mixing and drying of the lithium source, the iron source, the phosphorus source and the carbon source comprises:
[0015] The lithium source, the iron source and the phosphorus source are mixed, and then the carbon source is added to obtain a mixture;
[0016] wet grinding the mixed material to obtain a grind;
[0017] The ground material is spray-dried to obtain the premixed material.
[0018] Optionally, the wet grinding conditions include: a rotation speed of 800 to 1000 rpm and a time of 8 to 10 hours.
[0019] Optionally, the spray drying conditions include: a spray pressure of 0.3-0.5 MPa and a spray temperature of 120-150°C.
[0020] Optionally, when the lithium source, the iron source, the phosphorus source and the carbon source are mixed, the molar ratio of the iron element to the phosphorus element is (0.99-1.01):1, the molar ratio of the lithium element to the iron element is (0.95-1.05):1, and the weight ratio of the carbon source to the iron source is (0.06-0.1):1.
[0021] Optionally, the lithium source is selected from at least one of lithium hydroxide, lithium carbonate, lithium nitrate, and lithium hydrogen phosphate;
[0022] Optionally, the iron source is selected from at least one of iron phosphate and iron oxide;
[0023] Optionally, the phosphorus source is selected from at least one of iron phosphate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, and phosphoric acid;
[0024] Optionally, the carbon source is selected from at least one of polybutadiene, glucose and ascorbic acid.
[0025] Optionally, after sintering for the second time t2, the method further comprises: cooling and sieving the sintered product to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0026] The technical solution of the present invention has the following advantages:
[0027] The method for preparing a lithium iron phosphate positive electrode material provided by the present invention adopts a two-step sintering method for sintering, and optimizes the particle size of the lithium iron phosphate obtained by sintering by regulating the temperature and time of the two-step sintering, as well as the relationship between the temperature and time of the two-step sintering, so as to improve its conductivity and lithium ion diffusion coefficient while ensuring that its discharge capacity is not lost, thereby improving its rate performance.
[0028] Specifically, the stage of sintering at the first sintering temperature for the first time period is mainly a stage in which the lithium source is dehydrated into a molten state and reacts with the iron source and the phosphorus source. This stage can promote the lithium source, iron source and phosphorus source to form more crystal nuclei, thereby effectively reducing the growth of primary particles. If the first sintering temperature is too high, the nucleation rate will be too fast. If the first sintering temperature is too low, the reaction cannot occur. If the first time period is too long, the synthesized lithium iron phosphate material will have more internal defects.
[0029] Sintering at the second sintering temperature for the second time can make the primary particles formed in the first sintering process grow, thereby improving the crystallinity of the lithium iron phosphate material; if the second sintering temperature is too low and the second time is too short, the crystallinity of the lithium iron phosphate material will deteriorate, the material crystal form will not be complete, and the structure will be unstable; if the second sintering temperature is too high and the second time is too long, the particles of the lithium iron phosphate material will become larger, and part of the lithium iron phosphate will be reduced to Fe2P, resulting in poor conductivity of the lithium iron phosphate material.
[0030] In addition, experimental studies have found that when the result of (T2 / T1-1.3)×t2 / t1 is in the range of 0.2-3.5, the lithium iron phosphate material obtained by two-step sintering has excellent rate performance, and the smaller the result, the better the rate performance of the lithium iron phosphate material. DETAILED DESCRIPTION
[0031] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0032] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.
[0033] Example 1
[0034] The lithium iron phosphate positive electrode material was prepared as follows:
[0035] (1) adding lithium hydroxide and iron phosphate into a grinding machine hopper at a molar ratio of 1:1, adding polybutadiene after mixing, so that the mass ratio of polybutadiene to iron phosphate is 0.08:1, and then wet grinding at a speed of 1000 rpm for 8 hours to obtain a grinding material;
[0036] (2) spray drying the ground material obtained in step (1) at 135° C. and 0.4 MPa pressure to obtain a premixed material with a particle size D50 of 4 μm;
[0037] (3) heating the premixed material obtained in step (2) to 500° C. at a heating rate of 2° C. / min in a nitrogen atmosphere, and sintering at 500° C. for 6 h to obtain a pre-sintered product;
[0038] (4) The pre-sintered product obtained in step (3) is further heated to 660° C. at a heating rate of 3° C. / min, and sintered at 660° C. for 6 h. The product is cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0039] In this embodiment, the first sintering temperature T1=500° C., the first time t1=6 h, the second sintering temperature T2=660° C., the second time t2=6 h, and (T2 / T1-1.3)×t2 / t1=0.02.
[0040] Example 2
[0041] The lithium iron phosphate positive electrode material was prepared as follows:
[0042] (1) lithium hydroxide and iron phosphate are added into a grinding machine hopper at a molar ratio of 1:1. Then polybutadiene and iron phosphate are wet-ground at a mass ratio of 0.08:1 at a speed of 1000 rpm for 8 h to obtain a grinding material;
[0043] (2) spray drying the ground material obtained in step (1) at 135° C. and 0.4 MPa pressure to obtain a premixed material with a particle size D50 of 4 μm;
[0044] (3) heating the premixed material obtained in step (2) to 450° C. at a heating rate of 2° C. / min in a nitrogen atmosphere, and sintering at 450° C. for 4 h to obtain a pre-sintered product;
[0045] (4) The pre-sintered product obtained in step (3) is further heated to 680° C. at a heating rate of 3° C. / min, and sintered at 680° C. for 8 h. The product is cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0046] In this embodiment, the first sintering temperature T1=450° C., the first time t1=4 h, the second sintering temperature T2=680° C., the second time t2=8 h, and (T2 / T1-1.3)×t2 / t1=0.42.
[0047] Example 3
[0048] The lithium iron phosphate positive electrode material was prepared as follows:
[0049] (1) adding lithium hydroxide and iron phosphate into a grinding machine hopper at a molar ratio of 1:1, adding polybutadiene after mixing, so that the mass ratio of polybutadiene to iron phosphate is 0.08:1, and then wet grinding at a speed of 1000 rpm for 8 hours to obtain a grinding material;
[0050] (2) spray drying the ground material obtained in step (1) at 135° C. and 0.4 MPa pressure to obtain a premixed material with a particle size D50 of 4 μm;
[0051] (3) heating the premixed material obtained in step (2) to 400° C. at a heating rate of 2° C. / min in a nitrogen atmosphere, and sintering at 400° C. for 2 h to obtain a pre-sintered product;
[0052] (4) The pre-sintered product obtained in step (3) is further heated to 700° C. at a heating rate of 3° C. / min, and sintered at 700° C. for 10 h. The product is cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0053] In this embodiment, the first sintering temperature T1=400° C., the first time t1=2 h, the second sintering temperature T2=700° C., the second time t2=10 h, and (T2 / T1-1.3)×t2 / t1=2.25.
[0054] Example 4
[0055] The lithium iron phosphate positive electrode material was prepared as follows:
[0056] (1) adding lithium hydroxide and iron phosphate into a grinding machine hopper at a molar ratio of 1:1, adding polybutadiene after mixing, so that the mass ratio of polybutadiene to iron phosphate is 0.08:1, and then wet grinding at a speed of 1000 rpm for 8 hours to obtain a grinding material;
[0057] (2) spray drying the ground material obtained in step (1) at 135° C. and 0.4 MPa pressure to obtain a premixed material with a particle size D50 of 4 μm;
[0058] (3) heating the premixed material obtained in step (2) to 400° C. at a heating rate of 2° C. / min in a nitrogen atmosphere, and sintering at 400° C. for 6 h to obtain a pre-sintered product;
[0059] (4) The pre-sintered product obtained in step (3) is further heated to 800° C. at a heating rate of 3° C. / min, and sintered at 800° C. for 6 h. The product is cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0060] In this embodiment, the first sintering temperature T1=400° C., the first time t1=6 h, the second sintering temperature T2=800° C., the second time t2=6 h, and (T2 / T1-1.3)×t2 / t1=0.70.
[0061] Example 5
[0062] The lithium iron phosphate positive electrode material was prepared as follows:
[0063] (1) adding lithium hydroxide and iron phosphate into a grinding machine hopper at a molar ratio of 1:1, adding polybutadiene after mixing, so that the mass ratio of polybutadiene to iron phosphate is 0.08:1, and then wet grinding at a speed of 1000 rpm for 8 hours to obtain a grinding material;
[0064] (2) spray drying the ground material obtained in step (1) at 135° C. and 0.4 MPa pressure to obtain a premixed material with a particle size D50 of 4 μm;
[0065] (3) heating the premixed material obtained in step (2) to 500° C. at a heating rate of 2° C. / min in a nitrogen atmosphere, and sintering at 500° C. for 2 h to obtain a pre-sintered product;
[0066] (4) The pre-sintered product obtained in step (3) is further heated to 660° C. at a heating rate of 3° C. / min, and sintered at 660° C. for 10 h. The product is cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0067] In this embodiment, the first sintering temperature T1=500° C., the first time t1=2 h, the second sintering temperature T2=660° C., the second time t2=10 h, and (T2 / T1-1.3)×t2 / t1=0.10.
[0068] Comparative Example 1
[0069] The lithium iron phosphate positive electrode material was prepared as follows:
[0070] (1) adding lithium hydroxide and iron phosphate into a grinding machine hopper at a molar ratio of 1:1, adding polybutadiene after mixing, so that the mass ratio of polybutadiene to iron phosphate is 0.08:1, and then wet grinding at a speed of 1000 rpm for 8 hours to obtain a grinding material;
[0071] (2) spray drying the ground material obtained in step (1) at 135° C. and 0.4 MPa pressure to obtain a premixed material with a particle size D50 of 4 μm;
[0072] (3) heating the premixed material obtained in step (2) to 300° C. at a heating rate of 2° C. / min in a nitrogen atmosphere, and sintering at 300° C. for 10 h to obtain a pre-sintered product;
[0073] (4) The pre-sintered product obtained in step (3) is further heated to 660° C. at a heating rate of 3° C. / min, and sintered at 660° C. for 6 h. The product is cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0074] In this comparative example, the first sintering temperature T1=300°C, the first time t1=10h, the second sintering temperature T2=660°C, the second time t2=6h, and (T2 / T1-1.3)×t2 / t1=0.54.
[0075] Comparative Example 2
[0076] The lithium iron phosphate positive electrode material was prepared as follows:
[0077] (1) adding lithium hydroxide and iron phosphate into a grinding machine hopper at a molar ratio of 1:1, adding polybutadiene after mixing, so that the mass ratio of polybutadiene to iron phosphate is 0.08:1, and then wet grinding at a speed of 1000 rpm for 8 hours to obtain a grinding material;
[0078] (2) spray drying the ground material obtained in step (1) at 135° C. and 0.4 MPa pressure to obtain a premixed material with a particle size D50 of 4 μm;
[0079] (3) heating the premixed material obtained in step (2) to 600° C. at a heating rate of 2° C. / min in a nitrogen atmosphere, and sintering at 600° C. for 2 h to obtain a pre-sintered product;
[0080] (4) The pre-sintered product obtained in step (3) is further heated to 660° C. at a heating rate of 3° C. / min, and sintered at 660° C. for 6 h. The product is cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0081] In this comparative example, the first sintering temperature T1=600°C, the first time t1=2h, the second sintering temperature T2=660°C, the second time t2=6h, (T2 / T1-1.3)×t2 / t1=-0.60.
[0082] Comparative Example 3
[0083] The lithium iron phosphate positive electrode material was prepared as follows:
[0084] (1) adding lithium hydroxide and iron phosphate into a grinding machine hopper at a molar ratio of 1:1, adding polybutadiene after mixing, so that the mass ratio of polybutadiene to iron phosphate is 0.08:1, and then wet grinding at a speed of 1000 rpm for 8 hours to obtain a grinding material;
[0085] (2) spray drying the ground material obtained in step (1) at 135° C. and 0.4 MPa pressure to obtain a premixed material with a particle size D50 of 4 μm;
[0086] (3) heating the premixed material obtained in step (2) to 500° C. at a heating rate of 2° C. / min in a nitrogen atmosphere, and sintering at 500° C. for 6 h to obtain a pre-sintered product;
[0087] (4) The pre-sintered product obtained in step (3) is further heated to 600° C. at a heating rate of 3° C. / min, and sintered at 600° C. for 15 h. The product is cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0088] In this comparative example, the first sintering temperature T1=500°C, the first time t1=6h, the second sintering temperature T2=600°C, the second time t2=15h, (T2 / T1-1.3)×t2 / t1=-0.25.
[0089] Comparative Example 4
[0090] The lithium iron phosphate positive electrode material was prepared as follows:
[0091] (1) adding lithium hydroxide and iron phosphate into a grinding machine hopper at a molar ratio of 1:1, adding polybutadiene after mixing, so that the mass ratio of polybutadiene to iron phosphate is 0.08:1, and then wet grinding at a speed of 1000 rpm for 8 hours to obtain a grinding material;
[0092] (2) spray drying the ground material obtained in step (1) at 135° C. and 0.4 MPa pressure to obtain a premixed material with a particle size D50 of 4 μm;
[0093] (3) heating the premixed material obtained in step (2) to 500° C. at a heating rate of 2° C. / min in a nitrogen atmosphere, and sintering at 500° C. for 6 h to obtain a pre-sintered product;
[0094] (4) The pre-sintered product obtained in step (3) is further heated to 900° C. at a heating rate of 3° C. / min, and sintered at 900° C. for 5 h. The product is cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0095] In this comparative example, the first sintering temperature T1=500°C, the first time t1=6h, the second sintering temperature T2=900°C, the second time t2=5h, (T2 / T1-1.3)×t2 / t1=0.42.
[0096] Comparative Example 5
[0097] (1) adding lithium hydroxide and iron phosphate into a grinding machine hopper at a molar ratio of 1:1, adding polybutadiene after mixing, so that the mass ratio of polybutadiene to iron phosphate is 0.08:1, and then wet grinding at a speed of 1000 rpm for 8 hours to obtain a grinding material;
[0098] (2) spray drying the ground material obtained in step (1) at 135° C. and 0.4 MPa pressure to obtain a premixed material with a particle size D50 of 4 μm;
[0099] (3) The premixed material obtained in step (2) was heated to 660° C. at a heating rate of 2° C. / min in a nitrogen atmosphere, and sintered at 660° C. for 6 h. The premixed material was cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
[0100] Experimental example
[0101] The lithium iron phosphate prepared in Examples 1-5 and Comparative Examples 1-5 was used as the positive electrode active material, and the positive electrode active material, carbon black conductive agent, binder PVDF and NMP were prepared in a weight ratio of 95:2.5:2.5:5 to prepare a positive electrode slurry. The positive electrode slurry was coated on an aluminum foil with a thickness of 20 μm, and vacuum dried and rolled to form a sheet with a surface density of 8 g / cm 2 The positive electrode sheet is then used as the lithium metal sheet as the negative electrode and 1.15M LiPF6 EC:DMC (1:1 vol%) as the electrolyte; the button battery is assembled according to the conventional method.
[0102] The button cells prepared above were tested using a blue electric tester at a test temperature of 25°C and a test voltage range of 2.0V to 3.75V. The specific test method is as follows:
[0103] The prepared button cell was placed in an oven at 25°C for charge and discharge tests with a voltage range of 2.0V-3.75V, 0.1C charge and discharge for one cycle of activation, and then charged at 0.5C constant current and constant voltage, with a cut-off current of 0.05C, and discharged at 1C current for 50 cycles to obtain the first discharge specific capacity, the 50th cycle capacity retention rate and other data. The test results are shown in Table 1.
[0104] Table 1 Electrical performance test results of button batteries
[0105]
[0106] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The specific steps are as follows: The lithium source, the iron source, the phosphorus source and the carbon source are mixed and dried to obtain a premixed material; In a protective gas atmosphere, heating the premixed material to a first sintering temperature T1 at a first heating rate, and sintering at the first sintering temperature T1 for a first time t1 to obtain a pre-sintered product; Heating the pre-sintered product to a second sintering temperature T2 at a second heating rate, and sintering at the second sintering temperature T2 for a second time t2; Among them, 400℃≤T1≤500℃, 2h≤t1≤6h, 660℃≤T2≤680℃, 6h≤t2≤10h, and 0.2≤(T2 / T1-1.3)×t2 / t1≤3.5; After sintering for the second time period t2, the sintered product is cooled and sieved to obtain a lithium iron phosphate positive electrode material with a particle size of 4 μm to 8 μm.
2. The method according to claim 1, characterized in that 400℃≤T1≤450℃, 4h≤t1≤6h, 6h≤t2≤8h.
3. The method according to claim 1 or 2, characterized in that: The first heating rate is 1 to 3°C / min; And / or, the second heating rate is 2-4°C / min.
4. The method according to claim 1 or 2, characterized in that: The particle size D50 of the premixed material is 4 μm to 8 μm.
5. The method according to claim 1 or 2, characterized in that: The lithium source, iron source, phosphorus source and carbon source are mixed and dried, and the specific operation is as follows: The lithium source, the iron source and the phosphorus source are mixed, and then the carbon source is added to obtain a mixture; wet grinding the mixed material to obtain a grind; The ground material is spray-dried to obtain the premixed material.
6. The method according to claim 5, characterized in that The wet grinding conditions include: a rotation speed of 800 to 1000 rpm and a time of 8 to 10 hours.
7. The method according to claim 5, characterized in that The spray drying conditions include: a spray pressure of 0.3-0.5 MPa and a spray temperature of 120-150°C.
8. The method according to claim 5, characterized in that When the lithium source, the iron source, the phosphorus source and the carbon source are mixed, the molar ratio of the iron element to the phosphorus element is 0.99-1.01:1, the molar ratio of the lithium element to the iron element is 0.95-1.05:1, and the weight ratio of the carbon source to the iron source is 0.06-0.1:
1.
9. The method according to claim 5, characterized in that The lithium source is selected from at least one of lithium hydroxide, lithium carbonate, lithium nitrate and lithium hydrogen phosphate; And / or, the iron source is selected from at least one of iron phosphate and iron oxide; And / or, the phosphorus source is at least one selected from iron phosphate, dilithium hydrogen phosphate, lithium dihydrogen phosphate, and phosphoric acid; And / or, the carbon source is selected from at least one of polybutadiene, glucose and ascorbic acid.
Citation Information
Patent Citations
Preparation method for lithium ion secondary battery positive pole active substance lithium iron phosphate
CN101209823A